Cohort profile: the Swedish Maternal Microbiome project (SweMaMi) – assessing the dynamic associations between the microbiome and maternal and neonatal adverse events. Issue 10 (26th October 2022) - Fransson, Emma; Gudnadottir, Unnur; Hugerth, Luisa W; Itzel, Eva Wiberg; Hamsten, Marica; Boulund, Fredrik; Pennhag, Alexandra; Du, Juan; Schuppe-Koistinen, Ina; Brusselaers, Nele; Engstrand, Lars
Abstract : Purpose: The Swedish Maternal Microbiome (SweMaMi) project was initiated to better understand the dynamics of the microbiome in pregnancy, with longitudinal microbiome sampling, shotgun metagenomics, extensive questionnaires and health registry linkage. Participants: Pregnant women were recruited before the 20th gestational week during 2017–2021 in Sweden. In total, 5439 pregnancies (5193 unique women) were included. For 3973 pregnancies (73%), samples were provided at baseline, and for 3141 (58%) at all three timepoints (second and third trimester and postpartum). In total, 38 591 maternal microbiome samples (vaginal, faecal and saliva) and 3109 infant faecal samples were collected. Questionnaires were used to collect information on general, reproductive and mental health, diet and lifestyle, complemented by linkage to the nationwide health registries, also used to follow up the health of the offspring (up to age 10). Findings to date: The cohort is fairly representative for the total Swedish pregnant population (data from 2019), with 41% first-time mothers. Women with university level education, born in Sweden, with normal body mass index, not using tobacco-products and aged 30–34 years were slightly over-represented. Future plans: The sample and data collection were finalised in November 2021. The next steps are the characterisation of the microbial DNA and linkage to the health and demographic information from the questionnaires and registries. The role of the microbiome on maternal and neonatal outcomes and early-childhood diseases will be explored (including preterm birth, miscarriage) and the role and interaction of other risk factors and confounders (including endometriosis, polycystic ovarian syndrome, diet, drug use). This is currently among the largest pregnancy cohorts in the world with longitudinal design and detailed and standardised microbiome sampling enabling follow-up of both mothers and children. The findings are expected to contribute greatly to the field of reproductive health focusing on pregnancy and neonatal outcomes.